Singapore’s growth story: Leadership and innovation - NATHAN, S. R. (Institutional Knowledge at Singapore Management University, 2014)
The sixth president of the Republic of Singapore, S.R. Nathan, talks about leadership and innovation as the key foundation stones in Singapore’s growth story in this interview with Rajendra Srivastava.